Measurement of the VH,H → ττ process with the ATLAS detector at 13 TeV - Aad, Georges; Baltes, Lisa Marie; Bartels, Falk; Czurylo, Marta; Rio, Fernando del; Dittmeier, Sebastian; Dunford, Monica; Franchino, Silvia; Junkermann, Thomas; Klassen, Martin; Mkrtchyan, Tigran; Ott, Philipp; et al. (Physics letters, 2024)
A measurement of the Standard Model Higgs boson produced in association with a W or Z boson and decaying into a pair of τ-leptons is presented. This search is based on proton-proton collision data collected at s=13 TeV by the ATLAS experiment at the LHC corresponding to an integrated luminosity of 140 fb−1. For the Higgs boson candidate, only final states with at least one τ-lepton decaying hadronically (τ→hadrons+ντ) are considered. For the vector bosons, only leptonic decay channels are considered: Z→ℓℓ and W→ℓνℓ, with ℓ=e,μ. An excess of events over the expected background is found with an observed (expected) significance of 4.2 (3.6) standard deviations, providing evidence of the Higgs boson produced in association with a vector boson and decaying into a pair of τ-leptons. The ratio of the measured cross-section to the Standard Model prediction is μVHττ=1.28−0.29+0.30(stat.)−0.21+0.25(syst.). This result represents the most accurate measurement of the VH(ττ) process achieved to date.
The ATLAS Collaboration: G. Aad, L.M. Baltes, F. Bartels, Marta Czurylo, F. Del Rio, S.J. Dittmeier, M. Dunford, S. Franchino, T. Junkermann, M. Klassen, T. Mkrtchyan, P.S. Ott, D.F. Rassloff, S. Rodriguez Bosca, C. Sauer, A. Schoening, H-C. Schultz-Coulon, V. Sothilingam, R. Stamen, P. Starovoitov, L. Vigani, S.M. Weber, M. Wessels, J. Zinsser [und viele weitere]
Gesehen am 10.10.2025